2021
DOI: 10.3390/diagnostics11101838
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rapid Test to Detect Anti-SARS-CoV-2 N Protein IgG Based on Shear Horizontal Surface Acoustic Wave (SH-SAW)

Abstract: Since the Coronavirus disease 2019 (COVID-19) pandemic outbreak, many methods have been used to detect antigens or antibodies to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), including viral culture, nucleic acid test, and immunoassay. The shear-horizontal surface acoustic wave (SH-SAW) biosensor is a novel pathogen detection platform with the advantages of high sensitivity and short detection time. The objective of this study is to develop a SH-SAW biosensor to detect the anti-SARS-CoV-2 nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 37 publications
(47 reference statements)
0
21
0
Order By: Relevance
“…With developments in biosensing technology, SAW has been developed with precise control for promising utility in biosensors. For instance, the shear-horizontal surface acoustic wave (SH-SAW) biosensor is an inventive pathogen detection platform for detecting the anti-SARS-CoV-2 nucleocapsid antibody (IgG-based) [ 118 ]. Although there are still cases of poor sensitivity and an inability to detect small molecules, Yao et al, developed a method for quantifying Escherichia coli L-asparaginase by immobilizing amide-coupled polyclonal antibodies, which significantly improved sensitivity [ 119 , 120 ].…”
Section: Biosensors For the Detection Of Iggmentioning
confidence: 99%
“…With developments in biosensing technology, SAW has been developed with precise control for promising utility in biosensors. For instance, the shear-horizontal surface acoustic wave (SH-SAW) biosensor is an inventive pathogen detection platform for detecting the anti-SARS-CoV-2 nucleocapsid antibody (IgG-based) [ 118 ]. Although there are still cases of poor sensitivity and an inability to detect small molecules, Yao et al, developed a method for quantifying Escherichia coli L-asparaginase by immobilizing amide-coupled polyclonal antibodies, which significantly improved sensitivity [ 119 , 120 ].…”
Section: Biosensors For the Detection Of Iggmentioning
confidence: 99%
“…Apart from the detection of proteins, Brugger et al [ 114 ] reported the use of SAW for monitoring the formation of neural networks and some investigation for real-time monitoring of living matter, such as organoids or other biomaterials, along with the addition that innovative nanodrugs for efficiency and/or toxicity evaluation can also be imagined [ 115 ]. Since the COVID-19 pandemic began, some SAW-based sensors for COVID virus detection have also been reported [ 116 , 117 ].…”
Section: Current Applicationsmentioning
confidence: 99%
“…Surface acoustic wave (SAW) biosensors have been used to detect various biomarkers with high selectivity, high sensitivity, and low cost [ 11 , 12 ]. Our previous study showed that shear-horizontal surface acoustic wave (SH-SAW) biosensors can measure anti-SARS-CoV-2 N protein antibodies with good sensitivity [ 13 ]. The SH-SAW biosensor contains an input and output interdigital transducer (IDT), a sensing area coated with antibodies or antigens of the target molecules, and a reflector.…”
Section: Introductionmentioning
confidence: 99%